2017
DOI: 10.2147/ppa.s144961
|View full text |Cite
|
Sign up to set email alerts
|

Medication nonadherence among South American patients with schizophrenia

Abstract: ObjectiveThe objective of this research was to quantify nonadherence to medication and explore the determinants of nonadherence in patients diagnosed with schizophrenia (SZ) from three countries in Latin America (Bolivia, Peru, and Chile).MethodsThis study was conducted in public mental health centers in Bolivia, Peru, and Chile. The data collected included drug attitude inventory (DAI-10), sociodemographic information, and clinical and treatment characteristics of patients with SZ. Multivariate analysis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
2
6
1
Order By: Relevance
“…There are several moderating factors for poor attitude towards medication. The moderating factors were younger age [5, 8], male in sex [5, 19], being employed [20–22], urban residence, and living alone, which have a negative relationship with attitude towards medication [22]. Poor attitude towards antipsychotic medication was more common among patients with schizophrenia with a shorter duration of illness (less than five years) [8, 21, 23, 24], later age at onset of illness [25], and having frequent psychiatric hospital admissions [26].…”
Section: Introductionmentioning
confidence: 99%
“…There are several moderating factors for poor attitude towards medication. The moderating factors were younger age [5, 8], male in sex [5, 19], being employed [20–22], urban residence, and living alone, which have a negative relationship with attitude towards medication [22]. Poor attitude towards antipsychotic medication was more common among patients with schizophrenia with a shorter duration of illness (less than five years) [8, 21, 23, 24], later age at onset of illness [25], and having frequent psychiatric hospital admissions [26].…”
Section: Introductionmentioning
confidence: 99%
“… 10 However, a previous study (part of the larger International Research Project) showed a difference between the countries involved in this research where patients in Chile reported greater adherence to medication. 13 This last point can be explained by the Mental health policies in Chile, where there is a program Garantías Explícitas en Salud (GES) (Explicit Health Guarantees) that constitute a set of benefits guaranteed by law for individuals diagnosed with schizophrenia and other disorders, which ensures the delivery of antipsychotic medication to the patient, unlike Peru and Bolivia, where access to medication is not universal for the population of patients diagnosed with schizophrenia. 50…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Non-adherence is considered a complex phenomenon, which could be influenced by four factors: sociodemographic variables, psychotic symptomatology (including persecutory delusion, hostility, and cognitive impairment), variables related to treatment (frequency and intensity of side effects, subjective feeling under treatment, comorbid addiction, duration of treatment, and addictive behavior), and insight into the disorder. [12][13][14][15] Quality of life (QoL) is severely impaired in patients diagnosed with schizophrenia. 16 QoL and adherence to antipsychotics in patients have been studied extensively and independently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations